Ouvidorias públicas das universidades federais brasileiras: um benchmarking baseado no modelo de maturidade de ouvidoria pública (MMOup) - Rospirski, Andressa (2024)
The Public Ombudsman Maturity Model (MMOuP) was developed by the Office of the Comptroller General (CGU) as a reference tool for Ombudsman Offices, aiming to assist in the process of improving management. Organized into four dimensions that group the major objectives of an ombudsman office, the model allows the measurement of organizational maturity through scales that simplify and guide the organization of information. It establishes a desirable level of maturity, based on current regulations, and promotes self-diagnosis as a learning process, contributing to effective action in the improvement process. This study explores the possibility of comparing performance, practices, and processes among the Ombudsman Offices of Federal Universities, aiming to identify practices that can be adopted by similar institutions. The objective of the research is to support the development of the maturity levels of the Ombudsman Office of the Federal University for Latin American Integration (UNILA), using as a reference the self-diagnosis levels of other Public Ombudsman Offices of Brazilian Federal Universities, through the technique of Benchmarking. The research is applied in nature, adopting an exploratory and descriptive approach, and employs a mixed-methods methodology, both qualitative and quantitative. The data collection and analysis commence with document review, followed by secondary data gathering, and presents findings from the first cycle of the MMOuP, spanning March 2021 to March 2023, highlighting the 55 Federal Universities Ombudsman Offices. The data are presented in quantitative and statistical formats, such as charts and tables, complemented by descriptive content. results focus on the thirteen target elements listed in UNILA's action plan and include a pilot study on one of the selected elements. The analysis of the pilot element aims to categorize and understand the practices adopted and identify the evidence that supports the maturity levels chosen by the eighteen institutions selected in the benchmarking. Thus, the research demonstrated in an applied manner the theoretical-methodological feasibility and highlighted the advantages of benchmarking in the studied context, as the tool allows the identification and adoption of best practices from other entities that have already overcome similar challenges. The use of the MMOuP in benchmarking is particularly emphasized, as it provides an organized performance evaluation framework, facilitating the understanding of where the organization stands in terms of maturity and providing a common reference, optimizing data and information collection.